Hindsight Bias and Trust in Government: Evidence from the United States - Holger Herz; Deborah Kistler; Christian Zehnder; Christian Zihlmann (Center for Economic Studies and ifo Institute (CESifo), 2022)
We empirically assess whether hindsight bias has consequences on how citizens evaluate their political actors. Using an incentivized elicitation technique, we demonstrate that people systematically misremember their past policy preferences regarding how to best fight the Covid-19 pandemic. At the peak of the first wave in the United States, the average respondent mistakenly believes they supported significantly stricter restrictions at the onset of the first wave than they actually did. Exogenous variation in the extent of hindsight bias, induced through random assignment to survey structures, allows us to show that hindsight bias causally reduces trust in government.
Keywords: D72; D83; D91; 330; hindsight bias; trust in government; evaluation distortion; biased beliefs